Animals in Social Work
XXII, 246 p.
Keywords: This collection of essays articulates theoretical and philosophical arguments, and advances practical applications, as to why animals ought to matter to social work, in and of themselves. It serves as a persuasive corrective to the current invisibility of animals in contemporary social work practice and thought.